Continuity in a parameter of solutions to linear boundary-value problems in Hölder–Zygmund spaces - Murach, A.A.; Soldatov, V.O. (Reports of the National Academy of Sciences of Ukraine, 2016)
We introduce and investigate the broadest class of linear boundary-value problems for the systems of first-order ordinary differential equations, whose solutions belong to the complex Hölder–Zygmund space. For these problems, we establish a constructive criterion, under which their solutions are continuous in a parameter in this space.